P126 Frailty in hospitalised COPD patients. (December 2018) - Fei, L; Fraser, J; Padmanaban, V; Boniface, A; Wyman, E; Maguire, M; Stone, M; Elkin, S; Mallia, P
Abstract : Background: Chronic obstructive pulmonary disease (COPD) patients have multiple comorbidities and a high prevalence of frailty. Frailty is associated with increased hospital readmissions. Frailty increases length of stay (LOS) in patients admitted to acute medical units but has not been studied in COPD. There are conflicting results with regards to the effects of comorbidities on LOS in COPD. We examined relationships between frailty, comorbidities and LOS in COPD patients admitted to a London hospital trust with an acute exacerbation (AECOPD). Methods: The Rockwood Clinical Frailty score was recorded for 222 patients admitted with AECOPD between February 2017 and December 2017. This data was collated and referenced via the National COPD auditing tools. The medical records of a subset of 70 patients were examined to investigate whether the Frailty/Care of the Elderly medical teams were involved in their care. Results: 222 COPD patients (48% male) with an age range from 43–94 years were admitted during this time period. LOS ranged from 0–50 days (mean LOS 6.1 days, median LOS 5 days). The median Rockwood score was 5 (1 subject had a score of 1 and 4 subjects had a score of 9). LOS increased with increasing Rockwood score (figure 1), mean LOS was 3.27 days in patients with a score of 2 compared with 10.86 in patients with a score of 8 (p=0.038). There were weak but significant correlations between Rockwood score and LOS (r=0.26, p<0.0001) and number of comorbidities (r=0.19, p=0.025). Out of 70 patients, only 22 (31.4%) were reviewed by Frailty/Care of the Elderly team. The median Rockwood score of those not reviewed was 4, and 5 in those reviewed (p=0.06). Discussion: There is a correlation between Rockwood frailty score and LOS in hospitalised COPD patients. Patients admitted with COPD exacerbation are not routinely seen by physicians with expertise in frailty and it is not clear how decisions are made as to which patients are seen. The Rockwood Frailty Score can identify those patients that may require greater integrated health and social care interventions and service adaption to facilitate Frailty Team review may improve outcomes for these patients.